Shifts in High-Tech Trade Between Leader-Countries and Developing Countries - MATYUSHENKO, Igor; BERENDA, Sergiy; Grigorova-BERENDA, Larisa; SHOLOM, Alina; MARCHENKO, Ivan (Journal of Advanced Research in Law and Economics, 2019)
The purpose of the article is to study the state of trade in high-tech products of technological leaders with developing countries, and to create recommendations for developing countries to improve the development of trade in high-tech products with countries-leaders. Nowadays high-tech production and high-tech trade enter into the picture, when it comes to satisfying our needs. It generates an increase in global production of goods and services in developed countries, such as the USA and Canada, as well as in developing countries, such as Ukraine, Mexico, Brazil, and others. It is determined that high-tech exports show whether countries have an advantage in high-tech trade in comparison with other countries, which is a qualitative characteristic of high-tech exports. A functional block diagram of the research of high-tech trade in Ukraine, USA, Canada, Mexico and Brazil was created and presented, with the help of which further calculations were carried out. A regression and correlation analysis were carried out on the basis of high-tech exports of Ukraine, USA, Canada, Mexico and Brazil. Ukraine has a negative coefficient of comparative advantage in high-tech trade (-1.10), along with Canada (-0.19) and Brazil (-0.08), while the USA’s and Mexico’s coefficients are positive, 0.57 and 0.07 representatively. The article also highlights the prospects of development of high-tech trade in the countries considered.